การเคลือบอีนาเมลบนเหล็กแผ่นรีดเย็นเกรด SPCC ที่ผ่านการลดปริมาณคาร์บอน - มารุต บุญประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this thesis was to study porcelain enamel coating on decaburized SPCC cold rolled steel sheet by 2 coat/2 fire process. Pickling time was varied in the range of 2 6 minutes. Nickel dipping time was varied in the range of 0 to 8 minutes. The firing temperature was 820 ํC and firing time were 3 and 4 minutes for both coating processes. Microstructure at the interface of enamel and steel as well as cementite particles was investigated by light microscope. EDS and X-ray mapping method were used to analyze chemical composition at the interface. Mechanical adherence was determined by impact deformation test following ASTM B 916-01 standard and microstructure adherence was determined by anchor point count method. Coating surface defects were determined by visual inspection. It was found that pickling time did not make any significant change on the roughness of interface in the specimens without nickel dipping. In the group of nickel dipping specimen, the roughness of steel interfaces decrease when pickling time increase. Nickel dipping improved the adherence of enamel and steel. Nickel dipping for suitable time gave anchor type due to corrosion along steel surfaces in the firing stage, which cause good adherence of enamel and steel. Nickel dip for 4 minutes was suitable time in this experiment. Firing time at 820 ํC for 4 minutes gave better corrosion of steel interface than firing for 3 minutes due to complete corrosion at the steel interface. Surface defect was found on SPCC steel sheet coating due to gas evolution.